Implementasi Pisanc Chiper Untuk Autentikasi Voice Chat - Muhammad Fajar Rizky; Muhammad Syahrizal; Soeb Aripin (Journal of Computer System and Informatics (JoSYC), 2021)
In securing voice messages, information sent through the internet network must be authenticated for its authenticity, data content, delivery time, and so on. To prevent data manipulation by irresponsible parties, the creation of a data leak that has a negative impact. The occurrence of data leaks that most users are still not aware of. This can happen due to the lack of security of the message itself which results in problems that arise and also losses by certain authoritarian parties. The solution in securing voice messages using modern cryptographic techniques that have been combined with NRZI encoding and the Feistel network by Pisanc Cipher, is a way to maintain the authenticity and accuracy of data or authentication in voice messages. It is useful to look for the characteristics of good encryption, namely confusion and diffusion. This results in a higher level of security. By using the Pisanc Cipher method to secure voice messages, it can generate security and authenticate data to prevent data leakage. In addition, another benefit of using the Pisanc Cipher method is to maintain the authenticity of voice messages.